PENINGKATAN KOMPETENSI GURU DALAM MENGAJAR TEMATIK MELALUI PEER TEACHING PADA GURU DI SDN 01 MUARA PANAS - Yelvarina, Yelvarina (STKIP Pesisir Selatan, 2019)
This research originated from the fact that the teacher's ability in thematic teaching in the class was not good enough to overcome this matter the headmaster held peer teaching. This type of research is school action research (scholl action research), research uses qualitative and quantitative approaches. The research procedure consists of: planning stage, implementation phase, observation stage, and reflection stage. The research data was obtained from teacher competency assessment in the material study by observing all teaching activities through peer teaching. The results of the study showed that the teacher's ability to teach through peer teaching was proven by the teacher's competence in thematic teaching and was 86.6% in the second cycle. The activity of school principals in implementing peer teaching carried out the activity of the principal of the first cycle 69.2%. implemented after being reflected increased to 93.35% carried out in cycle II. After being reflected, an increase in the second cycle of teacher competence in thematic teaching can be increased to the activities of teachers in peer teaching. The first cycle of 68.75% was implemented after being reflected to increase to 86.63%. carried out in cycle II. From the analysis of the research it can be concluded that through peer teaching it can improve the competence of teachers in teaching at SDN 01 Muara Panas